Tannins from cashew tree (Anacardium occidentale) bark as a flocculant for water clarification - Anjos, Bruna Ferreira dos [UNESP]; Azevêdo, Tatiane Kelly Barbosa de; Silva, Bruna Rafaella Ferreira da; Braga, Renata Martins; Pimenta, Alexandre Santos; Andrade, Francisca Adriana Ferreira de (My University, 2022)
Concern about the overexploitation of natural resources has increased in recent decades, especially involving water and its treatment. Paradoxically, one of the sources of water pollution is the treatment itself, due to the use of chemical flocculants, which end up generating sludge that may be highly aggressive to the environment. One of the ways to solve this problem is to use natural flocculants for this purpose, since they are biodegradable and do not harm nature. This study evaluated the efficiency of a natural flocculant produced from tannins extracted from the bark of the cashew tree (Anacardium occidentale) and compared it with two commercial coagulants, Tanfloc® and iron chloride. The water for treatment was collected from a weir. The cashew trees’ bark was collected, ground, and submitted to hot-water extraction to yield the tannins, and the extraction product was cationized. The flocculation tests were carried out using the jar test with solutions having concentrations of 33.3, 66.7, and 100 mg L-1. Turbidity and pH were analyzed before and after flocculation. Among the assessed flocculants, the cationized tannins produced the best responses both for removal of turbidity and final pH of the treated water. Tanfloc® also produced satisfactory results regarding turbidity removal. The iron chloride, besides not properly clarifying the water, left it very acidic. Since the cationized tannins practically did not change the pH and were effective in the removal of turbidity, they represent an interesting, sustainable alternative product to treat the water.
Uso de taninos da casca de cajueiro (Anacardium occidentale) como floculante para remoção de turbidez de água
Keywords: cationized tannins; natural flocculating agente; removal of turbidity; water treatment